The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Companion to sexuality studies - Naples, Nancy A. (Wiley Blackwell, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

Santé sexuelle et autonomie reproductive : étude qualitative sur les expériences et représentations des femmes universitaires de Mumbai, Inde - Beauchemin-Roy, Sarah (Université du Québec à Montréal, 2018)
Cette recherche vise à explorer les expériences et représentations des femmes indiennes universitaires quant à leur santé sexuelle et reproductive. Plus précisément, il s'agit d'explorer les normes sociales et les enjeux associés à la décision d'avoir une vie sexuelle active ; de documenter les expériences et perceptions des femmes quant à leurs connaissances et à l'utilisation des méthodes de contraception ; et de décrire leur pouvoir de décision et de contrôle sur leur stratégie contraceptive. Pour y arriver, une recherche qualitative exploratoire a été menée de septembre à novembre 2016 à Mumbai, en Inde. Les 10 participantes sont des étudiantes au collège ou à l'université, sexuellement actives dans les douze derniers mois, âgées de 20 à 25 ans, qui ont pris part à une entrevue semi-dirigée de 60 minutes. Les résultats indiquent que les jeunes femmes universitaires font face à de nombreux obstacles à l'atteinte d'une autonomie reproductive et donc, d'une santé sexuelle et reproductive optimale. Tout d'abord, les normes patriarcales établies par les structures sociales et culturelles influencent les représentations de la sexualité féminine dans la société. Ensuite, quant aux expériences sexuelles des participantes, elles sont modulées par la famille et le réseau des pairs ; le premier étant un obstacle et le deuxième étant un facilitateur à la transgression des normes et des attentes sociales envers les femmes. Enfin, plusieurs facteurs interpersonnels et individuels élaborés dans ce mémoire jouent un rôle déterminant dans l'atteinte d'une autonomie reproductive. Pour conclure, il sera pertinent de se pencher sur les limites de cette recherche ainsi que sur des recommandations. Or, considérant que des changements majeurs sont nécessaires à plusieurs niveaux, des recommandations globales seront proposées. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : autonomie reproductive, santé sexuelle et reproductive, justice reproductive, méthodes contraceptives, étudiantes collégiales et universitaires, Mumbai, Inde
Keywords: 2000 à aujourd'hui; 2010-2019; IREF; asie; contraception; discipline; inde; justice reproductive; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; étudiantes indiennes

Pratiques masturbatoires féminines et santé sexuelle : une exploration qualitative des perspectives et des expériences des femmes - Morin, Valérie (Université du Québec à Montréal, 2018)
La sexualité des femmes a longtemps été réprimée et certaines études concluent qu'elles portent encore un regard négatif sur leur masturbation et leur droit au plaisir sexuel (Hogarth et Ingham, 2009; Kaestle et Allen, 2011). Ceci est problématique dans la mesure où un rapport négatif à son plaisir sexuel, et plus précisément à la masturbation, mine potentiellement la santé sexuelle. Or, les études sur la masturbation féminine réalisées à ce jour n'ont pas détaillé les processus impliqués dans le phénomène de la masturbation des femmes et ses liens multiples avec la santé sexuelle. Cette recherche qualitative exploratoire s'intéresse à savoir comment une pratique régulière de la masturbation (définie comme une fois par mois ou plus) module la santé sexuelle des femmes à travers le développement du concept de soi sexuel. Cette étude a analysé le discours de treize femmes (âgées de 18 à 30 ans) sur leurs pratiques masturbatoires et a tenté de décrire les processus sous-jacents à une sexualité plus épanouie et une meilleure santé sexuelle. Ces analyses ont été complétées en interprétant la perception des femmes de cette pratique à l'aide du concept de soi sexuel et de théories critiques féministes. Les résultats tendent à montrer que les femmes qui se masturbent régulièrement ont une meilleure compréhension de leur soi sexuel en raison d'une plus grande aisance et connaissance corporelle, d'une meilleure reconnaissance de leurs désirs et leurs besoins sexuels, et d'une plus grande confiance en leur capacité à obtenir un orgasme. De plus, en contexte dyadique, elles semblent témoigner d'une plus grande confiance, et ce grâce à une meilleure connaissance de leurs préférences sexuelles, une plus grande appropriation de leur plaisir sexuel, une meilleure communication de leurs désirs et besoins sexuels, et une plus grande volonté à essayer de nouvelles pratiques sexuelles. Bref, cette étude précise la place essentielle qu'occupe la masturbation dans la construction d'une sexualité saine et épanouie. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : masturbation, masturbation féminine, santé sexuelle, concept de soi sexuel, scripts sexuels, réflexivité sexuelle
Keywords: 2000 à aujourd'hui; 2010-2019; IREF; amériques; discipline; masturbation féminine; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Sex, desire and masturbation : An interpretative phenomenological analysis of sexual health education for young women - Hanson, Jodie (Manchester Metropolitan University, 2014)
British, Sex and Relationship Education has been condemned by Ofsted as ‘not yet good enough’ (2013:6). Previous literature would suggest this is through the absence of desire based knowledge. Other research would highlight the issue of masturbation as a construct to the improvement of the sexual health. However, as genital masturbation is often a taboo within feminine culture the current study used Interpretative Phenomenological Analysis (Smith, 1996, 1999) to assess the intrinsic values of six young women regarding their sexual health and desires. Participants ranged in sexual knowledge from undergone several years of sexual health education to limited sexual health education; forming the basis for the current national education system. Analysis of the data revealed three master themes: pleasure conflict, ‘That Girl’ complex and sexual discourse. A working model of sexual health needs was then proposed in order to address the hierarchy of erotic plasticity the participants showed. Ramifications of socio-political implications towards feminine desire and masturbation are detrimental to sexual health improvement.
https://e-space.mmu.ac.uk/576583/1/Jodie%20Hanson.pdf
Keywords: 2000 à aujourd'hui; 2010-2019; angleterre; discipline; europe; jeunes femmes*; masturbation féminine; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; éducation sexuelle; études qualitatives

How they got it and how they wanted it: Marginalised young people's perspective on their experiences of sexual health education - Brown, Graham; Sorenson, Anne; Hildebrand, Janina (Sex Education, 2012)
Young people in Australia are at greatest risk of contracting sexually transmitted infections, and priority actions are necessary for this population group. This study of marginalised and at-risk young people in out-of-school environments was conducted in Western Australia with the aim of obtaining young people's perceptions about their experience of sexual health education and preferred means of gaining sexual health knowledge and skills. A participatory research methodology was implemented through a series of workshops with 88 young people recruited through community youth agencies. The results of the study support what is already known about sexual health promotion for young people and the importance of a holistic approach to promoting positive relationships and sexual health. However, the findings emphasise that this should include the need for demonstrated trust, confidence and safe environments, and the complementary role of community youth agencies and peer-based programmes which may play an important role in reaching young people who may disengage with, or not be reached by school-based sexual health education.
Keywords: 2000 à aujourd'hui; 2000-2009; adolescentes*; australie; discipline; personnes marginalisées; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Identification des besoins de formation des enseignantes et des enseignants du secondaire en matière d'éducation à la sexualité dans le contexte de la réforme de l'éducation - Beaulieu, Nadine (Université du Québec à Rimouski, 2010)
L'objectif de cette étude est d'identifier les besoins de formation des enseignantes et des enseignants du secondaire en matière d'éducation à la sexualité en lien avec le contexte du renouveau pédagogique. Pour ce faire, nous avons élaboré et validé un questionnaire d'enquête de 36 questions que nous avons fait passer à 78 participants, tous enseignants au secondaire sur le territoire d'une commission scolaire du Bas-St-Laurent. Nos objectifs spécifiques sont plus précisément: 1) d'évaluer le niveau d'importance accordé par l'enseignant à chacune des six thématiques proposées par le MEQ et le MSSS en regard du mandat d'éducation à la sexualité auprès d'élèves de niveau secondaire; 2) d'évaluer le niveau de connaissances perçu de la part de l'enseignant en regard de la démarche d'éducation à la sexualité réalisée auprès d'élèves de niveau secondaire; 3) d'évaluer le niveau d'aisance perçu de la part de l'enseignant à aborder chacune de ces thématiques en regard de la démarche d'éducation à la sexualité réalisée auprès d'élèves de niveau secondaire; 4) d'identifier les liens possibles entre les différentes variables à l'étude. Les résultats de cette recherche démontrent que les participants reconnaissent l'importance d'une démarche d'éducation à la sexualité en milieu scolaire. Nous remarquons néanmoins que plus un enseignant avance en âge et moins il accorde de l'importance à l'éducation à la sexualité. De plus, les enseignants disent avoir un niveau de connaissances et d'aisance «satisfaisant» pour aborder les différentes thématiques suggérées par le MEQ-MSSS (2003). Par ailleurs, nous constatons une différence en ce qui a trait à la thématique «violence sexuelle» puisqu'elle est celle pour laquelle les participants accordent le plus d'importance, mais représente aussi celle pour laquelle ils disent en connaître le moins et être le moins à l'aise. Également, il apparaît que plus un enseignant accorde un niveau d'importance élevé à une thématique, plus ce dernier dit avoir un niveau élevé de connaissances et d'aisance. En conclusion, nous ferons état des pistes de réflexion quant à la formation des enseignants en matière d'éducation à la sexualité à l'intention des universités québécoises dispensant un baccalauréat en enseignement au secondaire (BES) ainsi qu'aux décideurs.
https://semaphore.uqar.ca/id/eprint/411/1/Nadine_Beaulieu_aout2010.pdf
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; discipline; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; stéréotypes de genre; thématiques; violences; violences sexuelles; éducation sexuelle; étude quantitative

Caution, the use of humor may lead to confusion :Evaluation of a video podcast of the midwest teen sex show - Campo, Shelly; Askelson, Natoshia M.; Spies, Erica L.; Losch, Mary (American Journal of Sexuality Education, 2010)
Web sites about sexual health lack the interactivity, humor, and “viral” nature required to attract young adults. The Midwest Teen Sex Show (www.midwestteensexshow.com) is an interactive, humor-based Web site that provides sexual health information to young adults. One episode from the Web site was shown to six focus groups of young women, ages 18-30. Women found it funny, but some were offended or confused. Women were unable to differentiate between facts and humor; however, women could identify the key messages. Most women reported they would think about it later, visit the Web site, and share it with friends. Web-based interventions should use humor with caution.
Keywords: amériques; communication; contraception; discipline; humour; jeunes femmes*; médias; ressource en ligne; régions géographiques; santé; santé reproductive; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative

Queer Diagnoses: Parallels and Contrasts in the History of Homosexuality, Gender Variance, and the Diagnostic and Statistical Manual - Drescher, Jack (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
The American Psychiatric Association (APA) is in the process of revising its Diagnostic and Statistical Manual (DSM), with the DSM-V having an anticipated publication date of 2012. As part of that ongoing process, in May 2008, APA announced its appointment of the Work Group on Sexual and Gender Identity Disorders (WGSGID). The announcement generated a flurry of concerned and anxious responses in the lesbian, gay, bisexual, and transgender (LGBT) community, mostly focused on the status of the diagnostic categories of Gender Identity Disorder (GID) (for both children and adolescents and adults). Activists argued, as in the case of homosexuality in the 1970s, that it is wrong to label expressions of gender variance as symptoms of a mental disorder and that perpetuating DSM-IV-TR’s GID diagnoses in the DSM-V would further stigmatize and cause harm to transgender individuals. Other advocates in the trans community expressed concern that deleting GID would lead to denying medical and surgical care for transgender adults. This review explores how criticisms of the existing GID diagnoses parallel and contrast with earlier historical events that led APA to remove homosexuality from the DSM in 1973. It begins with a brief introduction to binary formulations that lead not only to linkages of sexual orientation and gender identity, but also to scientific and clinical etiological theories that implicitly moralize about matters of sexuality and gender. Next is a review of the history of how homosexuality came to be removed from the DSM-II in 1973 and how, not long thereafter, the GID diagnoses found their way into DSM-III in 1980. Similarities and differences in the relationships of homosexuality and gender identity to psychiatric and medical thinking are elucidated. Following a discussion of these issues, the author recommends changes in the DSM-V and some internal and public actions that the American Psychiatric Association should take.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; inégalités; premier cycle; psychiatrie; régions géographiques; santé; sciences; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; transidentité; violences; états-unis

Young men, masculinities and sex education - Limmer, Mark (Sex Education : Sexuality, Society and Learning, 2010)
This paper draws on focus group and interview data from 45 young men from the north of England to explore the barriers to effective sex and relationships education (SRE). Recent policy debates in relation to establishing statutory SRE in schools provide an opportunity to revisit how it is currently delivered to, and received by, young men. The paper considers the central role played by masculinities and how this role is mediated by social exclusion and poor engagement; it is suggested that addressing masculinities directly should be a priority for future SRE. In conclusion, some tentative approaches to addressing the issues are suggested.
Keywords: 2000 à aujourd'hui; 2000-2009; angleterre; discipline; europe; hommes*; jeunes adultes; masculinité; périodes historiques; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle

A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

Critical intersex - Holmes, Morgan (Ashgate, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Section: 1 vol. (XIV-257 p.) ; 24 cm.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes

Breaking the taboo: An exploration of female university students' experiences of attending a feminist‐informed sex education course - Askew, Julie (Sex Education : Sexuality, Society and Learning, 2007)
This article presents the results of a qualitative interview study of nine young women who attended a feminist-informed human sexuality course as undergraduate students at a US university located in the "Bible belt". The course focused on messages of desire and empowerment, rather than romance or fear, and was designed to encourage students to think critically about current sexual discourses. Results indicate that participants' information on sexual issues prior to taking the course was limited and largely negative. Experiences of the course are described in themes including owning sexual desire, improved body image, reduced guilt and fear, and increased confidence as a woman. It is concluded that sex education may be used to help empower female students and enrich their quality of life; current educational practices should therefore be examined for ways in which they are oppressive to development.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; image corporelle; jeunes femmes*; pédagogie; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative